A novel freemium code SAND (v1.0) for generation of randomly packed beds - Shadymov, Nikita; Papkov, Viacheslav; Pashchenko, Dmitry (Particuology, 2024)
The main current approaches for generation of the packed bed models are based on rigid body dynamics (RBD) and Newton's laws (discrete element methods - DEM). This paper deals with the development and analysis of a novel code based on analytical geometry approach for the packed bed generation. The architecture and main algorithms of the novel code are described and clarified. The parameters of the packed bed generated via the novel code are compared with experimental data and packed beds generated via Blender (RBD), Yade (DEM). The novel code demonstrates many advantages, such as good correlation with experimental data, no overlaps between pellets in the packed bed, and a low computational time for packed bed generation. The packed bed model can be directly exported in .step format. Other advantages are also demonstrated and clarified. The novel code is attached to this paper and can be freely used by engineers and scientists. [Display omitted] •A novel freemium code for packed bed generation is now available.•This innovative code is based on an analytical geometry approach.•The main advantages of this novel code: rapid packed bed generation, no overlaps.•Pellets in the packed bed are represented using a minimal number of facets.•The SAND code has been uploaded for free use as supplementary material.